PERSONALIZED VIRTUAL SCHOOL ENVIRONMENT USING CLASSIFIER ALGORITHM AND SEMANTIC ADVISOR-ASSISTING FRAMEWORK - Maniyar, Jaimin; Livingston, Jenila (Asian Journal of Pharmaceutical and Clinical Research, 2017)
As we knew that every individual is different than each other and their brain levels are also different, some students are very bright and some are not, so there is a need to develop such system which will teach them as per their thought process and learning habits. This research aims to develop a personalized virtual school environment for students which help them to learn the things same as they learn in school physically, but the thing here is each student will be treated differently as per his/her ability. Hence, this system would be a virtual school for any student, which resembles the CBSE school system in India. In this virtual school, all things are present such as teachers, homework, games, and exams which present in actual school except one which is the physical classroom because in virtual environment the course and things are personalized for each student as per his/her thoughts and brain level, so here the student can seat in his/her home and can learn at any time with help of computer. The system is a webbased environment and machine learning would be used for doing personalization on family and knowledge context of student. This web system contains four components: (1) Classification based on family context, (2) classification based on knowledge context, (3) learning material selection algorithm, (4) web-based learning system on top of above three, are discussed in this paper. Â